Trends in nontraumatic subarachnoid hemorrhage-related mortality among young adult (15–64 years) population in the United States, 1999–2022 - Foley, Olivia; Rizvi, Syeda Aamna Ijtaba; Kensok, Thomas C.; Murugan, Vikram; Ashby, Anthony; Jabbar, Ali Bin Abdul; Mirza, Mohsin; Tauseef, Abubakar (Frontiers in Neurology, 2025)
BackgroundNontraumatic subarachnoid hemorrhages (NSAH) are the result of intracranial aneurysm rupture and involve bleeding into subarachnoid space. NSAH causes significant stroke burden among adults in the United States (US). Due to the unique challenges that younger adults (aged 15–64 years) may face, it is important to analyze NSAH-related mortality among this age group stratified to determine who is most at risk.MethodsMortality trends related to NSAH in adults aged 15–64 years old in the US between 1999 and 2022 were analyzed utilizing the Centers for Disease Control and Prevention Wide-ranging Online Data for Epidemiologic Research (CDC WONDER) database. Age-adjusted mortality rate (AAMR), annual percent change (APC), and average annual percent change (AAPC) were subsequently analyzed. Data was then stratified by sex, race, region, state, rural vs. urban classification, and age.ResultsBetween 1999 and 2022, there were 85,930 NSAH-related deaths among adults aged 15–64 years in the US, and overall AAMR decreased throughout the study period. Females had consistently higher AAMRs than males but demonstrated a larger overall decrease in mortality. Black or African American and American Indian or Alaskan Native patients had the highest NSAH-related AAMR between 1999 and 2022. NSAH-related mortality decreased in all regions of the US between 1999 and 2022, while individual states demonstrated a variety of trends. Urban and rural areas both saw declines in NSAH-related AAMR, while the 55–64-year age-group consistently displayed the highest NSAH-related crude mortality rates between 1999 and 2022.ConclusionDespite overall declines in mortality, persistent disparities in mortality across sex, race, and region highlight need for further study to decrease NSAH-related burden these groups overall.